Hypoxia enhances self-renewal properties and markers of mesenchymal stem cells - Yustianingsih, Vivi; Sumarawati, Titiek; Putra, Agung (Faculty of Medicine, Trisakti University, 2019)
BackgroundMesenchymal stem cells (MSCs) are multipotent stromal cells that express CD73, CD90, and CD105 surface markers, but not CD14, CD45, CD34, CD11b, and HLA-DR. MSCs under hypoxic conditions have the essential role of maintaining the stemness capacity by releasing several growth factors into their medium, known as hypoxia conditioned medium (HCM). This study was performed to compare the effect of percentage of HCM to normoxic medium (NM) in increasing MSC proliferation marked by proliferation rate and surface marker expression.MethodsThis study was of post-test only control group design using human umbilical cord-MSCs (hUC-MSCs) as subjects. The HCM treatment group was obtained by culturing MSCs under 5% O2, whereas the NM control group was grown under 20% O2. The hUC-MSCs were divided into 4 groups with different dose ratios of HCM to NM (25%:75%; 50%:50%; 75%:25% for P1, P2 and P3, respectively and 100% of NM for the controls). All of these groups were maintained at 37oC and the data was collected after 72 hours incubation. MSC marker expression of CD73, CD90 and CD105 was analyzed using flow cytometry and MSC proliferation by trypan blue assay. ResultThere were significant differences in MSC marker expression of CD73, CD90 and CD105 and proliferation at all dose ratios of HCM to NM (p<0.05).ConclusionLow oxygen concentration promotes MSC proliferation and stemness thus it might be beneficial for maintaining the MSC physiologic niche in-vitro.